Modeling the photochemical transformation of nitrobenzene under conditions relevant to sunlit surface waters: Reaction pathways and formation of intermediates - Vione, Davide; De Laurentiis, Elisa; Berto, Silvia; Minero, Claudio; Hatipoglu, Arzu; Cinar, Zekiye (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Nitrobenzene (NB) would undergo photodegradation in sunlit surface waters, mainly by direct photolysis and triplet-sensitized oxidation, with a secondary role of the (OH)-O-center dot reaction. Its photochemical half-life time would range from a few days to a couple of months under fair-weather summertime irradiation, depending on water chemistry and depth, NB phototransformation gives phenol and the three nitro phenol isomers, in different yields depending on the considered pathway. The minor (OH)-O-center dot role in degradation would make NB unsuitable as (OH)-O-center dot probe in irradiated natural water samples, but the selectivity towards (OH)-O-center dot could be increased by monitoring the formation of phenol from NB+(OH)-O-center dot. The relevant reaction would proceed through ipso-addition of (OH)-O-center dot on the carbon atom bearing the nitro group, forming a pre-reactive complex that would evolve into a transition state (and then into a radical addition intermediate) with very low activation energy barrier. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Nitrobenzene; Hydroxyl radical; Photo-oxidative degradation; DFT calculation; COSMO; LABORATORY MEASURES; TITANIUM-DIOXIDE; SOLAR LIGHT; DEGRADATION; OXIDATION; POLLUTANTS; MATTER; FATE; Environmental Sciences & Ecology